Dedi Mulyadi’s personal branding through “barracks” viral content - Hidayat, Dasrun; Lyndon, Novel Anak; Mujianto, Haryadi (PRofesi Humas, 2025)
Background: Social media has become a strategic medium for building political personal branding. Kang Dedi Mulyadi (KDM) utilizes platforms such as YouTube and TikTok to display a leadership style close to the community. One of his viral contents, “nanti dijemput ke barak (to be picked up to the barrack)”, reflects a personal branding strategy based on local cultural values. Purpose: This research analyzes KDM’s digital personal branding strategy against visual and verbal narratives in digital content and public responses. Methods: It uses a descriptive qualitative method with a cultural public relations approach, a communication approach that emphasizes aspects of West Javanese local culture in building and managing relationships. To collect the data, the study examined verbal and visual data on videos on KDM social media accounts. Results: Kang Dedi Mulyadi builds an image as a humanist leader, simple, and attached to Sundanese cultural values. The phrase ‘picked up to the ‘barracks’symbolizes the emotional closeness between the leader and the people. This strategy is effective because it combines populist approaches, local wisdom, and digital storytelling. Conclusion: KDM’s personal branding represents local culture in a communicative and modern way. Implications: The theoretical implications show the importance of integration between political and cultural communication. Meanwhile, this strategy can be a model for other public figures in building an authentic and relevant image in the digital space.